Nota sobre el concepto de demostración en C. S. Peirce - Legris, Javier (2012)
Charles Sanders Peirce developed in the last stage of his thought a conception of mathematical proof with roots in his own semiotic theory: proving is constructing an icon or diagram. The aim of this note is to make a brief but clear analysis of the notions that come into play in this conception and suggest its usefulness for the philosophy of mathematical practice.